The effect of hyperoxia on inflammation and platelet responses in an ex vivo extracorporeal membrane oxygenation circuit. Issue 12 (4th August 2020) - Passmore, Margaret R.; Ki, Katrina K.; Chan, Chris H. H.; Lee, Talvin; Bouquet, Mahé; Wood, Emily S.; Raman, Sainath; Rozencwajg, Sacha; Burrell, Aidan J. C.; McDonald, Charles I.; Langguth, Daman; Shekar, Kiran; et al.
Abstract: Use of extracorporeal membrane oxygenation (ECMO) is expanding, however, it is still associated with significant morbidity and mortality. Activation of inflammatory and innate immune responses and hemostatic alterations contribute to complications. Hyperoxia may play a role in exacerbating these responses. Nine ex vivo ECMO circuits were tested using fresh healthy human whole blood, with two oxygen levels: 21% inspired fraction of oxygen (FiO2 ; mild hyperoxia; n = 5) and 100% FiO2 (severe hyperoxia; n = 4). Serial blood samples were taken for analysis of platelet aggregometry, leukocyte activation, inflammatory, and oxidative stress markers. ECMO resulted in reduced adenosine diphosphate‐ ( P  < .05) and thrombin receptor activating peptide‐induced ( P  < .05) platelet aggregation, as well as increasing levels of the neutrophil activation marker, neutrophil elastase ( P  = .013). Additionally, levels of the inflammatory chemokine interleukin‐8 were elevated ( P  < .05) and the activity of superoxide dismutase, a marker of oxidative stress, was increased ( P  = .002). Hyperoxia did not augment these responses, with no significant differences detected between mild and severe hyperoxia. Our ex vivo model of ECMO revealed that the circuit itself triggers a pro‐inflammatory and oxidative stress response, however, exposure to supra‐physiologic oxygen does not amplify that response. Extended‐duration studies and inclusion of an endothelial component could be beneficial in characterizing longer term changes.